Modeling Philippine inflation using non-linear models; threshold autoregression and Markov Regime-Switching approaches - Gallentino Marc Victor F.
Abstract (Given the high impact of inflation on the poor household, inflation studies deserve more attention especially now that the Philippines is at the onset of TRAIN Law. This paper aims to study inflation rate in the Philippines using nonlinear models: 1 Threshold Autoregressive Model (TAR) and 2 Markov Regime-Switching Model (MSW). Using the Diesel price as the threshold variable, the TAR model for the change in Headline Inflation identified a threshold value of PHP 30.05, which is slightly lower than the estimated threshold of PHP 30.25 in the change in Bottom 30% Inflation model. Findings suggest that growth in price of Diesel has significant positive effect within the high inflation. The corresponding expected duration indicate that Headline Inflation and Bottom 30% Inflation are expected to stay in the high inflation period for 35 months and 11 months, respectively. As the current price of diesel is above the identified threshold, the imposed exercise tax in Diesel price due to TRAIN Law will have a 0.29 and a 0.27 percentage points impact on the change in Headline Inflation, the excise tax on Diesel price is expected to have a 0.14 and 0.15 percentage point impact on change in Headline Inflation and on Change in Bottom 30% Inflation, respectively. Policymakers should monitor inflation and direct government policies toward stabilizing prices).